PENGARUH PENGETAHUAN PERPAJAKAN, SISTEM ADMINISTRASI PERPAJAKAN MODERN DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI - May Sarah Hasibuan; Ai Hendrani (Jurnal Kelola: Jurnal Ilmu Sosial, 2022)
The purpose of this study is to examine and determine the factors that influence taxpayer compliance. The factors tested in this study were knowledge of taxation, modern tax administration systems and tax sanctions as independent variables while taxpayer compliance as the dependent variable. The sample in this study is an individual taxpayer of private employees who work in Central Jakarta sampling using nonprobability sampling method with the convenience sampling method, the research sample obtained as many as 100 respondents. The analytical method used is multiple linear regression analysis with statistical application tools. The results of hypothesis testing state that simultaneously the variables of tax knowledge, modern tax administration systems, and tax sanctions have an effect on taxpayer compliance. Partially, tax knowledge has a positive effect on mandatory compliance, modern tax administration systems have a positive effect on taxpayer compliance and tax sanctions have a positive effect on taxpayer compliance.